THE ROLE OF INTERCULTURAL DIALOGUE IN EUROPEAN UNION POLICY (PANGEEA, 2025)
ABSTRACT: European Union policy is based on cultural, religious and linguistic diversity, which encourages collaboration between Member States to improve knowledge of the culture of European Union. Due to the fact that there are various religious beliefs in European multicultural societies, and this mix of cultures can affect the EU's economic, social and political development, there needs to be an effective dialogue between people and cultures to make this cultural society work. This dialogue plays a fundamental role in building Europe where people live together, not just co-exist. It helps prevent racism, isolation and discrimination of immigrants. Intercultural dialogue has been strongly promoted within the EU by introducing cultural communities into public spaces and promoting inclusion by recognizing the culture of refugees and migrants. Its main purpose is to promote equality, human dignity and a sense of common purpose in order to increase tolerance and respect for the other. The EU Commission recommends the development of language projects to support intercultural dialogue, as knowledge of languages fosters professional insertion and mobility of people, creating the right framework for a better understanding of cultural diversity. Keywords: intercultural dialogue; cultural diversity; social participation; integration.
Keywords: intercultural dialogue; cultural diversity; social participation; integration